2017
DOI: 10.1097/imi.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Conduit Harvest in Coronary Artery Bypass Grafting Surgery

Abstract: Objective The purpose of this consensus conference was to develop and update evidence-informed consensus statements and recommendations on harvesting saphenous vein and radial artery via an open as compared with endoscopic technique by systematically reviewing and performing a meta-analysis of randomized and nonrandomized clinical trials. Methods All randomized controlled trials and nonrandomized controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 74 publications
2
10
0
Order By: Relevance
“…Only eight out of 2462 patients died in hospital or within 30 days, of which two underwent EAH and six underwent OAH. The in-hospital or 30-day mortality rate is insignificantly low for both groups, which supported the findings in the meta-analysis of Cao et al [49], Wu et al [48] and Ferdinand et al [51]. However, their studies lacked follow-ups of long-term survival, which is an important indicator to decide the surgical approach as the main purpose of CABG is to prevent the mortality caused by heart failure in the future.…”
Section: Plos Onesupporting
confidence: 76%
See 2 more Smart Citations
“…Only eight out of 2462 patients died in hospital or within 30 days, of which two underwent EAH and six underwent OAH. The in-hospital or 30-day mortality rate is insignificantly low for both groups, which supported the findings in the meta-analysis of Cao et al [49], Wu et al [48] and Ferdinand et al [51]. However, their studies lacked follow-ups of long-term survival, which is an important indicator to decide the surgical approach as the main purpose of CABG is to prevent the mortality caused by heart failure in the future.…”
Section: Plos Onesupporting
confidence: 76%
“…Three other meta-analysis studies have reported EAH to be beneficial for decreasing wound infections [7,50,51]. Our study included more literature and demonstrated the significant benefit for preventing wound infections (RR = 0.29, 95% CI = 0.14 to 0.60, p = 0.0009).…”
Section: Plos Onesupporting
confidence: 59%
See 1 more Smart Citation
“…These findings align strongly with the recent publication by Zenati and colleagues, who also demonstrate that there is no significant difference in rate of repeat re-vascularisation post CABG surgery between the EVH and OVH groups (HR, 0.79; 95% CI, 0.54 -1.17; p=0.25) 19 . Current evidence supports the use of endoscopic vein harvesting in multi vessel coronary artery disease 6, 9,24 and it is based on the effectiveness of these techniques, that the International Society of Minimally Invasive Cardiac Surgery consensus statements now recommend (class 1, Level B) that endoscopic vein harvesting should be standard of care for patients 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite a growing body of evidence demonstrating equivalent long-term cardiac outcomes between EVH and OVH and lower rates of wound complications with EVH, the question of which technique is superior remains controversial. EVH was endorsed as the standard of care for vein harvest for CABG by the International Society for Minimally Invasive Cardiothoracic Surgery in a 2005 consensus statement and affirmed this position in a 2015 update [ 45 ]. While the superiority of EVH for mitigation of wound complications appears to be settled, questions about the effect of EVH on long-term vein graft patency remain.…”
Section: Endoscopic Vs Open Saphenous Vein Harvestmentioning
confidence: 99%